Numerical and experimental studies on ship motions induced by passing ship - Pedro, Francisco G. (2019)
To investigate the ability of numerical models to simulate the behavior of moored ships subjected by ship-wake waves, use is made of scale model tests where a ship model sails with constant speed along a straight path at a constant distance from an otherwise motionless ship. The tests were carried out at one of the wave tanks of the Portuguese Civil Engineering Laboratory (LNEC). The moving ship is a self-propelled scale model of the "Aurora" chemical ship whereas the otherwise motionless ship is a scale model of the "Esso Osaka" tanker. The free-surface elevation was measured with a set of resistive wave gauges and ADVs. The tanker's movements, induced by the wake waves, were measured along the six degrees of freedom with a gyroscope deployed inside the ship. The numerical model WAMIT provides, in the frequency domain, the quantities required to estimate the hydrodynamic forces associated to the interaction of a free-floating ship with waves. The BAS model uses those hydrodynamic forces to study in the time domain the ship interaction with any sea-waves acting on it. Wind and current actions can also be accounted for. The results of these numerical models are compared to the measurements made in the several repeats of one of those scale model tests, in terms of the response amplitude to several wave components. These comparisons enabled the evaluation and validation of the numerical models parameters' calibration process.